Occupational characterization of professionals in Respiratory Therapy of the City of Guayaquil - SABANDO FAJARDO, EDWARDS (2020)
Respiratory Therapy is a health profession with high demand worldwide related to the current epidemiological profile of chronic degenerative diseases with cardio-respiratory care dependence. The present study tries to know the current occupational profile of the professionals in Respiratory Therapy of the city of Guayaquil. The method used for this article was he sent an electronic survey that addresses the occupational characteristics of the professionals of this discipline, who work in the city of Guayaquil. The results of the research were 55.60% of the respondents are between the ages of 26 and 35, only 3.70% have completed postgraduate studies, 22.50% have no employment relationship with health institutions and a 73.8% said they had a high degree of satisfaction with their current profession. It can be concluded that there are very few professionals with postgraduate studies. The occupational profile is oriented to work in hospitals with 77.50% and in carrying out activities such as oxygen therapy, aerosol therapy, aspiration of secretions and control of mechanical ventilation. Most professionals do not apply respiratory therapy protocols and do not participate in clinical decisions in patient care.